Silica supported sulfuric acid-catalysed one-pot processes for the synthesis of n-heterocycles - Ndagano, Urbain Nshokano (Rhodes University, Faculty of Science, Department of Chemistry)
Access restricted. Expected release in 2025.
Keywords: Uncatalogued